2017
DOI: 10.15446/dyna.v84n200.58518
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and control of the multihead weighing process through a modified control chart

Abstract: Los gráficos de control modificados se utilizan para el seguimiento y control de procesos de fabricación que son considerados como procesos seis-sigma. El uso de estos gráficos se basa en la idea de que el costo de identificar y corregir causas especiales de variación es mucho más alto que el costo de productos alejados de su valor nominal. Por lo tanto, la media del proceso es esencialmente aceptable siempre que esté dentro de los límites de especificación. Estos conceptos han sido aplicados al proceso de env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The w i weights in the hoppers are arranged in a normal distribution w i ∼ N(µ, σ) [14][15][16], where µ is the average weight of the product to be provided in each weighing hopper H Wi , and σ is the standard deviation. Previous studies have found that σ has a direct correlation with the mean quantity µ and linearly depends on it, due to vibrating feeding systems, according to σ = γµ; where γ is a proportionality coefficient and varies according to the characteristics of the packaging product [14][15][16][17]19].…”
Section: Weighing Process On Double-layered Upright and Diagonal Weig...mentioning
confidence: 99%
See 2 more Smart Citations
“…The w i weights in the hoppers are arranged in a normal distribution w i ∼ N(µ, σ) [14][15][16], where µ is the average weight of the product to be provided in each weighing hopper H Wi , and σ is the standard deviation. Previous studies have found that σ has a direct correlation with the mean quantity µ and linearly depends on it, due to vibrating feeding systems, according to σ = γµ; where γ is a proportionality coefficient and varies according to the characteristics of the packaging product [14][15][16][17]19].…”
Section: Weighing Process On Double-layered Upright and Diagonal Weig...mentioning
confidence: 99%
“…The second strategy (S 2 ) proposes diving the n weighing hopper into three groups, (n 1 , n 3 , n 5 ) and feeding different average quantities to each subgroup (µ 1 , µ 3 , µ 5 ), as per Equation (16). Finally, in the third strategy (S 3 ), the n weighing hoppers are filled with the same amount of product, µ = T k for each hopper, as expressed in Equation (17).…”
Section: Hopper-filling Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study compares these approaches by reviewing the effects of parameter estimates when monitoring problems that follow a gamma distribution, such as time between events and other asymmetric processes, with a CUSUM control chart design made for optimal performance when parameters are known. To motivate our research, we use the studies of García‐Díaz and Pulido‐Rojano 21 where measurements of multihead weightings from a packaging process approaches a gamma model and requires monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…La mejora continua en los procesos y productos se constituye como la clave para alcanzarla. Dentro de esta mejora continua, la calidad es sin duda pieza fundamental para satisfacer las expectativas de los clientes, de ahí que a través del tiempo las compañías busquen mecanismos para garantizarla y evitar productos defectuosos que se traduzcan en cuantiosas pérdidas, no solo a nivel financiero sino de imagen frente a los clientes [1][2][3][4].…”
Section: Introductionunclassified